Effects of some internal organizational factors on administrative decentralization in education at the MECS national capital region - Abad, Corazon Soliman
The subjects consisted of 34 administrators at the ministry, regional, division, and school levels and 220 public secondary school teachers selected through stratified random sampling. Data were gathered by means of questionnaire and analyzed using frequencies, percentages, means, standard deviation, Pearson product-moment correlation and stepwise regression analysis. Administrative decentralization is positively related to a.) age and leadership style of superior and followership style of subordinate at the regional level, and b.) age and leadership style of superior at the division level. Organization size is negatively related to the extent of administrative decentralization at the school level.
Thesis (D.Ed.)--University of the Philippines Diliman.
Keywords: Philippines -- Ministry of Education, Culture and Sports; School -- Decentralization